1999
DOI: 10.1021/la990259z
|View full text |Cite
|
Sign up to set email alerts
|

Force-Induced Dissociation of Single Protein A−IgG Bonds

Abstract: We investigated the force-induced dissociation of single specific bonds between biomolecules. For these experiments we used a micropipet-based picoforce transducer. It consisted of a red blood cell tensed by micropipet suction. The stiffness of this "spring" was tuned by suction pressure. The proteins under investigation were immobilized onto microbeads. One type of bead carried the adhesion proteins and was biochemically attached to the red blood cell membrane. The second type, carrying the respective ligand,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 43 publications
3
43
0
Order By: Relevance
“…The values of 0 and f 0 relative to the different experiments are given in Table 1. To get an idea of the sensitivity of the value of 0 to our experimental data, we represent in found for the dissociation rate in the case of various specific interactions of the type ligand͞receptor (9,16).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The values of 0 and f 0 relative to the different experiments are given in Table 1. To get an idea of the sensitivity of the value of 0 to our experimental data, we represent in found for the dissociation rate in the case of various specific interactions of the type ligand͞receptor (9,16).…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, Evans (15) showed that the rupture force measured in AFM spectroscopy should depend on the retraction rate. This was clearly demonstrated for ligand͞ receptor systems over the last year (7,9). A change of the retraction rate in AFM experiments thus gives access to the dynamics of proteins.…”
mentioning
confidence: 77%
See 2 more Smart Citations
“…We adjusted and optimized the immobilization of proteins on microbeads previously described in (Lofas and Johnsson, 1990;Johnsson et al, 1991) including some later adaptations (Strigl et al, 1999). The three main steps are bead dextranization, dextran carboxylation, and protein immobilization.…”
Section: Covalent Coupling Of Proteins To Microbeadsmentioning
confidence: 99%